Centenary conversations. (10th January 2022) - Clark, Helen; Yates, Robert
Abstract : Helen Clark is interviewed by Robert Yates for the first in a new series of 'Centenary conversations', celebrating 100 years of International Affairs. They discussed the COVID-19 crisis and reflect on whether the world is doing a better job than it did 100 years ago during the Spanish flu epidemic.